The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6ob01523a
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalyzed cascade allylic alkylation and dearomatization reactions of indoles with vinyloxirane

Abstract: We have developed Pd-catalyzed intermolecular Friedel-Crafts-type allylic alkylation and allylic dearomatization reactions of substituted indoles bearing a nucleophilic group with vinyloxirane, providing an efficient method to synthesize structurally diverse tetrahydrocarboline and spiroindolenine derivatives under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 38 publications
(2 reference statements)
0
8
0
1
Order By: Relevance
“…Friedel-Crafts-type allylic alkylation and dearomatization of the indole affords the product. 81 Compounds 198 were obtained in very good yields in the presence of 2.5 equivalents of Et 3 B as promoter and 1 equivalent of MgSO 4 as additive in THF at 50 °C. Taking advantage of the nucleophilicity of C-3 of the indole, and applying the same reaction conditions on dimethyl (3-indolylmethyl)malonate 199, but increasing the amount of Pd catalyst to 4 mol% and chang-ing the ligand to 8.5 mol% dppb, the allylic dearomatization afforded the spiroindolenine derivatives 200 with satisfactory yields and moderate diastereoselectivity (Scheme 82).…”
Section: Review Synthesismentioning
confidence: 99%
“…Friedel-Crafts-type allylic alkylation and dearomatization of the indole affords the product. 81 Compounds 198 were obtained in very good yields in the presence of 2.5 equivalents of Et 3 B as promoter and 1 equivalent of MgSO 4 as additive in THF at 50 °C. Taking advantage of the nucleophilicity of C-3 of the indole, and applying the same reaction conditions on dimethyl (3-indolylmethyl)malonate 199, but increasing the amount of Pd catalyst to 4 mol% and chang-ing the ligand to 8.5 mol% dppb, the allylic dearomatization afforded the spiroindolenine derivatives 200 with satisfactory yields and moderate diastereoselectivity (Scheme 82).…”
Section: Review Synthesismentioning
confidence: 99%
“…The product of the dearomatization reaction 200 and its precursor 198 (R=Cl) have the same polarity; therefore, for their separation, indolenine 200 was converted into the corresponding less polar indoline (54 %) (Scheme 52). [236] A synthetic scheme has been proposed that allows, along with annealing, also carrying out the spirolinking of the cyclopropane fragment to the cyclohex [a]indole backbone. Stirring the diketone 201 with 2 equiv.…”
Section: The Indole Dearomatization Strategy In the Synthesis Of Spirmentioning
confidence: 99%
“…The product of the dearomatization reaction 200 and its precursor 198 (R=Cl) have the same polarity; therefore, for their separation, indolenine 200 was converted into the corresponding less polar indoline (54 %) ( Scheme 52). [236] …”
Section: Syntheses Of Spiroheterocycles From 3‐alkylidene‐indol‐2‐onementioning
confidence: 99%
“…Next, further optimization of the reaction conditions was carried out using L1 (Table 1). Reactions in various solvents, such as DMF,C H 2 Cl 2 ,a nd THF,a fforded comparable yields and enantioselectivity albeit with lower 3a/4a ratios (entries 2-4), whereas MeOH and PhMe led to almost no reaction (entries [5][6]. Further evaluation of the concentration( entries 7-11) of 1a revealed that c = 0.2 mol L À1 was optimal in terms of yield (entry 8).…”
mentioning
confidence: 99%
“…[3,4,5] Recently,w er ealized the construction of fused indolenine skeletons in ac ascadef ashion. [6] In 2014, the Rawal group and we independently reported an intermolecular cascade dearomatization reactiono fi ndole-based bisnucleophiles with propargyl carbonate, leading to aseries of spiroindolenines andspiroindolines. Moderate enantioselectivity ( 77 % ee)w as achieved for limited substrates (Scheme1,reaction 1).…”
mentioning
confidence: 99%